570. The Effects of Locus of Control, Social Support, and Stigma on the HIV Care Continuum in the Aging HIV-Infected Population. (26th November 2018) - Mashiak, Christopher; Chan, Grace; Steffens, David; Chirch, Lisa M
Abstract: Background: Locus of control (LOC), or how one perceives one's control over a situation, can affect health outcomes, including outcomes of HIV care. Our research goal was to determine how social factors such as LOC affect patients' progression through the HIV care continuum, focusing on the experiences of older HIV-infected individuals. Methods: A convenience sample of English-speaking, HIV-infected patients was surveyed at UConn Health. The survey included assessments of internal LOC (ILOC), external LOC (ELOC), social support, depression, HIV stigma, and, and Ryan White (RW) funding status. Outcome measures marking progress through the care continuum, including appointment history, HIV viral load, and CD4 count, were obtained from chart review. Engagement in care was defined as attendance at ≥2 appointments and no missed appointment in the previous year. Results: A total of 58 subjects were enrolled from June to November 2016. The mean age was 52.4 years (range 24–84), 78% were ≥50 years old, 57% were male, and 47% received RW funding. Table 1 shows associations between study outcomes and social support, LOC and HIV stigma. Among older subjects, engagement in care was associated with less social support ( P = 0.04). Among subjects with significant depressive symptoms, lower ILOC was associated with engagement in care ( P < 0.001) and CD4 counts ≥350 ( P = 0.01). Neither patient age nor RW funding status had significant impact with respect to study outcomes. Conclusion: Older HIV-infected patients had similar study outcomes compared with their younger peers. Low social support, higher ELOC, and lower ILOC were associated with better outcomes despite being associated with more depression, possibly due to increased reliance on health professionals. These measures could be useful to screen for patients who are less likely to remain in the HIV care continuum. Disclosures: All authors: No reported disclosures.